2022
DOI: 10.2991/assehr.k.220207.014
|View full text |Cite
|
Sign up to set email alerts
|

The Design of Maternal Health Status Report System to Decrease Maternal Mortality in Jember Regency

Abstract: Jember is the regency with the highest Maternal Mortality Rate (MMR) in East Java. In 2019, MMR of Jember Regency was the 5th highest rank with 133.4/100,000 KH. Therefore, efforts are needed to reduce maternal mortality in Jember Regency. The purpose of this study was to create a system for recording pregnant women as an effort to reduce maternal mortality in Jember Regency. This type of research is research and development research with SDLC method. The results of this study are an application of the materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
0
0
1
Order By: Relevance
“…This results are relevant to the previous research conducted by Damayanti et al who stated that a paper-based system poses a great deal of difficulty in ensuring data accuracy as this system has a limited life after a certain period due to space limitations [14]. Moreover, some of the clinicians, particularly the doctors, indicated that typing information in a computer could be similar to writing on a paper, and typing speed could be increased through practice and training [11]. Therefore, the development of computer-based information systems would facilitate data storage and retrieval fast and enable intelligent processing or data compilation to provide accurate and quick benefit for patients.…”
Section: System Investigationsupporting
confidence: 67%
See 1 more Smart Citation
“…This results are relevant to the previous research conducted by Damayanti et al who stated that a paper-based system poses a great deal of difficulty in ensuring data accuracy as this system has a limited life after a certain period due to space limitations [14]. Moreover, some of the clinicians, particularly the doctors, indicated that typing information in a computer could be similar to writing on a paper, and typing speed could be increased through practice and training [11]. Therefore, the development of computer-based information systems would facilitate data storage and retrieval fast and enable intelligent processing or data compilation to provide accurate and quick benefit for patients.…”
Section: System Investigationsupporting
confidence: 67%
“…The EHR standard is being developed in Indonesia and relates mainly to hospital-based environments although some data may also come from the community healthcare centers. Research conducted in a district of Central Java shows that the Banyumas district integrated the reporting and recording systems of several primary health centers with a computer system (using a Local Area Network close to a WAN) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Model air terjun (waterfall) kadang dinamakan siklus hidup klasik (classic life cycle), dimana hal ini menyiratkan pendekatan yang sistematis dan berurutan (sekuensial) pada pengembangan perangkat lunak. Yang dimulai dengan spesifikasi kebutuhan pengguna dan berlanjut melalui tahapan-tahapan perencanaan (planning), pemodelan (modeling), konstruksi (construction), serta penyerahan sistem/perangkat lunak ke pelanggan/pengguna (deployment), yang diakhiri dengan dukungan berkelanjutan pada perangkat lunak lengkap yang dihasilkan [6].…”
Section: Metode Pengembangan Sistemunclassified